Alternative assessment of knee joint muscle balance of soccer players through total work-based hamstring: quadriceps ratios - Minozzo, F.; Lopez, P.; Figueiredo Machado, C. L.; Wilhelm, E. N.; Grazioli, R.; Silveira Pinto, R. (European Journal of Sport Science, 2018)
Isokinetic hamstring-to-quadriceps (H:Q) ratios are frequently used to assess knee muscle strength imbalances and risk of injuries/re-injuries. The use of peak torque (PT) or total work (TW) to estimate joint stability may lead to different results because of the differences between these two neuromuscular variables. Thus, the current study aimed to compare the conventional and functional H:Q ratios calculated by PT and TW. Ninety-three male professional soccer players from Brazilian first division teams performed isokinetic concentric and eccentric contractions of the quadriceps and the hamstrings at 60°/s. Muscle strength balance was calculated using the conventional torque ratio (CTR) and conventional work ratio (CWR), functional torque ratio (FTR) and functional work ratio (FWR) were highly and moderately correlated between them (r = 0.83 and r = 0.73, respectively). The Wilcoxon statistical test revealed significant differences between CTR and CWR, as well as FTR and FWR (p < 0.05). T-test demonstrated significant differences in mean CTR-CWR and FTR-FWR, whereas Bland-Altman plots showed non-consistent bias. In addition, the chi-square test demonstrated significant differences between players below the conventional reference values and functional reference values (p < 0.001). In conclusion, TW ratios seem to provide distinct and additional information regarding the H:Q strength balance in professional soccer players. Moreover, taking into account that TW captures torque information throughout the entire range of motion, it is possible that TW ratios represent a more comprehensive assessment of muscle strength imbalance.